Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.36469/jheor.2021.22256
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness and Budget Impact of Emerging Minimally Invasive Surgical Treatments for Benign Prostatic Hyperplasia

Abstract: Background: Benign prostatic hyperplasia (BPH) is one of the most prevalent and costly chronic conditions among middle-aged and elderly men. Prostatic urethral lift (PUL) and convective water vapor thermal therapy (WVTT) are emerging minimally invasive surgical treatments as an alternative to traditional treatment options for men with moderate-to-severe BPH. This study evaluated the cost-effectiveness and budget impact of PUL and WVTT for men with BPH using long-term clinical outcomes. Methods: The cost-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…One economic analysis compared cost-effectiveness between six BPH treatments (combination prescription drug therapy, Rezum, conductive radiofrequency thermal therapy [Prostiva], UroLift, Greenlight PVP, and TURP 49 ), while the other compared cost-effectiveness between Rezum and UroLift. 50 Both analyses found Rezum to be more cost-effective when compared to UroLift, 49,50 and the analysis comparing Rezum to the five other BPH treatment options concluded Rezum to be the most cost-and clinically effective treatment for BPH. 49 Therefore, Rezum warrants consideration to be offered as a first-line treatment, alternative to prescription drug therapy, in men seeking relief in LUTS secondary to BPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One economic analysis compared cost-effectiveness between six BPH treatments (combination prescription drug therapy, Rezum, conductive radiofrequency thermal therapy [Prostiva], UroLift, Greenlight PVP, and TURP 49 ), while the other compared cost-effectiveness between Rezum and UroLift. 50 Both analyses found Rezum to be more cost-effective when compared to UroLift, 49,50 and the analysis comparing Rezum to the five other BPH treatment options concluded Rezum to be the most cost-and clinically effective treatment for BPH. 49 Therefore, Rezum warrants consideration to be offered as a first-line treatment, alternative to prescription drug therapy, in men seeking relief in LUTS secondary to BPH.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two Markov model cost‐effectiveness analyses on BPH treatments were conducted to determine the best use of health care funds and clinical benefits for patients with BPH. One economic analysis compared cost‐effectiveness between six BPH treatments (combination prescription drug therapy, Rezum, conductive radiofrequency thermal therapy [Prostiva], UroLift, Greenlight PVP, and TURP 49 ), while the other compared cost‐effectiveness between Rezum and UroLift 50 . Both analyses found Rezum to be more cost‐effective when compared to UroLift, 49,50 and the analysis comparing Rezum to the five other BPH treatment options concluded Rezum to be the most cost‐ and clinically effective treatment for BPH 49 .…”
Section: Discussionmentioning
confidence: 99%
“…These procedures may have lower costs related to anaesthesia and inpatient care, but data are insufficient to suggest if they are more cost effective than TURP 1516…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 99%
“…As part of the Cochrane Urology group, we published a network meta-analysis in 2021 on effectiveness of minimally invasive treatments compared with TURP in men with BPE. This included trials in Cochrane reviews on these individual treatments over the past two years 11121516. For this article, we have drawn largely from the network meta-analysis.…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 99%
“…As an outpatient or officebased setting without general anaesthesia, it offers lasting relief from LUTS.38 For moderate-to-severe LUTS associated with BPH, Mcvary KT et al concluded in their study that WVTT was the treatment approach of choice when compared to PUL in terms of cost and effectiveness, due to its lesser technical and retreatment expenses. 39 Transurethral Needle Ablation (TUNA): Transurethral needle ablation (TUNA) is a minimally invasive procedure for the treatment of symptomatic benign prostatic hyperplasia (BPH). 40 It employs subordinate radiofrequency energy to trigger discerning necrosis of the hyperplastic prostatic tissue while conserving the urethra and neighbouring structures.…”
Section: Surgical Treatmentmentioning
confidence: 99%